Protein composition-functionality relationships using novel genetic lines - Jonnala, Ramakanth S (Kansas State University, 2008)
Novel genetic materials were used to deduce gluten protein composition-functionality relationships. The Pegaso bread wheat near-isogenic lines (NILs) included addition, variation and/or deletion of major loci coding for HMW-GS, LMW-GS and gliadins. The waxy wheat lines (Svevo and N11 set) included wild, partial and complete waxy lines. Triticale translocations include 1R.1D and 1A.1D lines (GDS7, Trim, Rhino and Rigel sets) with HMW-GS 5+10 and 2+12. The main goal of the study was to establish the usefulness of NILs as appropriate materials to investigate the structure-function relationships of wheat proteins and to evaluate the performance of unique triticale translocations and waxy wheat lines. Effect of genetic variation on phytochemical (phenolic acid and policosanol) contents was also studied. Innovative methods like MALLS, Lab-on-a-chip and micro (10 g) baking were utilized along with traditional analytical methods. Results confirmed the potential of using NILs in understanding the effects of certain proteins coded at specific loci that might often be targeted in breeding programs. Removal of expected chain terminators at Gli-1/Gli-2 loci causes a shift in MWD to higher values, reflected in higher UPP and dough strength. Lines with HMW-GS 5+10 were clearly separated from 2+12 lines in terms of dough strength and UPP. The present study obtained evidence that modified ω-gliadins acts as chain terminators and cause reduction of protein polymer size and thus shifts in MWD. Marked differences in terms of milling characteristics, protein composition and ultimately in end-use functionality were observed with various waxy wheat null lines. Loaf volumes with waxy wheat flour alone were higher than a 50% blend with commercial wheat; however, breads were unacceptable to consumers in all aspects. Poor milling quality, very low mixing times with low bread loaf volumes were typical of all the triticales studied. However, translocation of the HMW-GS from wheat chromosome 1D increased dough strength, particularly the HMW-GS 5+10. Among the phytochemicals studied, double nulls at Gli-1 loci of Pegaso NILs had the highest total policosanols and total phenolic acid contents.Slight variation to wheat phenolic acid composition and contents were observed with waxy wheat and triticale lines.
Keywords: Near-isogenic lines; Protein composition-functionality; Waxy wheat; Triticale; Molecular weight distribution; Chain terminators; Agriculture, Food Science and Technology (0359)